PENERAPAN GREENSHIP HOMES DENGAN PERINGKAT GOLD PADA RUMAH TYPE 36 - Ardafa, M. Fahrel; Alfajari, Muhammad Hafizh; Nuraini, Cut; Andriana, Melly; Ginting, Windu Terkelin (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The increase in housing development in Indonesia often faces environmental sustainability challenges. To overcome this, the concept of greenship homes was introduced as a solution that supports environmentally friendly, energy-efficient, and sustainable housing. This study aims to implement the Greenship Homes standard with the target of achieving the Gold rating on type 36 houses. The research method involves literature study, energy simulation, and quantitative and qualitative analysis of home design elements. This research focuses on energy and air use efficiency, waste management, the use of environmentally friendly materials, and the maintenance of natural waste. The results show that through certain design strategies, type 36 homes can qualify for a Gold rating in the Greenship Homes system. This implementation not only has a positive impact on the environment, but also increases the comfort of residents and the economic value of the property. This research is a practical guide for developers and architects to realize more sustainable housing in the future.